2019
DOI: 10.3390/jcm9010051
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics to Go beyond the Canonical Effect of Acetylsalicylic Acid

Abstract: Given to its ability to irreversibly acetylate the platelet cyclooxygenase-1 enzyme, acetylsalicylic acid (ASA) is successfully employed for the prevention of cardiovascular disease. Recently, an antitumoral effect of ASA in colorectal cancer has been increasingly documented. However, the molecular and metabolic mechanisms by which ASA exerts such effect is largely unknown. Using a new, untargeted liquid chromatography–mass spectrometry approach, we have analyzed urine samples from seven healthy participants t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…We were able to detect many of the metabolites in aspirin-related pathways profiled in previous studies on other diseases, such as downregulated metabolites in glutamate and histidine metabolism pathways 35,36 and decreased LC-PUFA dihomo-linolenate (20:3n3 or n6; HMDB0002925) in oxylipid synthesis. 37 At the same time, we also found metabolic changes that were less often linked to aspirin, for example, an increase of arachidonic acid-containing lipids including lysophospholipid, phosphatidylcholine, and phosphatidylinositol (Figure 1C, Table S3).…”
Section: Discussionmentioning
confidence: 72%
“…We were able to detect many of the metabolites in aspirin-related pathways profiled in previous studies on other diseases, such as downregulated metabolites in glutamate and histidine metabolism pathways 35,36 and decreased LC-PUFA dihomo-linolenate (20:3n3 or n6; HMDB0002925) in oxylipid synthesis. 37 At the same time, we also found metabolic changes that were less often linked to aspirin, for example, an increase of arachidonic acid-containing lipids including lysophospholipid, phosphatidylcholine, and phosphatidylinositol (Figure 1C, Table S3).…”
Section: Discussionmentioning
confidence: 72%
“…The authors suggested that the metabolic outcome of aspirin in vivo may depend on the expression of thioesterases that hydrolyze acetylsalicylic acid (aspirin) to salicylic acid since they found an opposite effect of salicylic acid on 3H-palmitate oxidation. Aspirin-mediated activation of fatty acid oxidation was further confirmed through the analysis of human urine samples collected after 7 days of aspirin treatment [ 50 ]. Promotion of FA oxidation upon aspirin treatment is consistent with the reported AMPK activation and resulting deactivation of ACC [ 46 , 47 ], because the catalytic product of ACC2 isoform malonyl-CoA is the natural inhibitor of CPT1A [ 28 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QTOF-MS) analysis was performed using ultra-highperformance liquid chromatography system (1290 InfinityII; Agilent) coupled to a quadrupole time-of-flight mass spectrometry detector (6545; Agilent) outfitted with an electrospray ionization (ESI) source. LC-QTOF-MS method, performance evaluation, data processing, and acyl-carnitine identification and analysis were performed as a published report with minor modifications (48). In brief, a sample (2 μL) was injected into Waters XSelect HSS T3 chromatographic column (2.5 μm; 100 × 2 mm), maintained at 25 °C.…”
Section: Methodsmentioning
confidence: 99%